The Effects of Calcium Fertilizer Sprays during Fruit Development Stage on Pineapple Fruit Quality under Humid Tropical Climate - Supriyono Loekito; null Afandi; Auliana Afandi; Naomasa Nishimura; Hiroyuki Koyama; Masateru Senge (International Journal of Agronomy)
Low calcium content in pineapple could decrease its quality, such as fruit translucency (electrolyte leakage), bruises (fruit firmness), and the other fruit quality standards. The purpose of the current study was to assess the effect of different sprays of calcium (Ca) fertilizer sources during the fruit development stage on the overall fruit quality. Four sources of calcium, chelated calcium, calcium nitrate (Ca(NO3)2), calcium chloride (CaCl2), each in 75 kg ha−1, and calcium boron (calcibor) of 10 L ha−1 mixed with 2000 L water, were directly sprayed onto individual fruit and crown, 75, 85, 95, and 105 days after forced flowering induction (forcing). The Smooth Cayenne “MD-2” pineapple cultivar was utilized for the experiment in a randomized complete block design with four replications and conducted at two different times. Fruit quality analyses were carried out on the harvested fruits 140 days after forcing. The application of calcium sprays did not have significant effects on fruit pH, total soluble solids, total acidity, fruit firmness, and the content of sucrose and vitamin C. There was a different response of calcium spray in the first and second trials on the content of glucose, fructose, β-carotene, Ca, and Mg, probably due to climate condition. All treatments with calcium sprays reduced the fructose and glucose contents in the first trial and β-carotene content in the second trial. Calcium chloride and calcibor increased Ca and decreased electrolyte leakage significantly than the other treatments. The scanning electron microscope analysis revealed that CaCl2 sprays generated greater turgor and more rigidity in the pineapple cell wall. The result showed that the application of CaCl2 and calcibor sprays could decrease electrolyte leakage incidence in pineapple with any potential to reduce glucose, fructose, and β-carotene without influencing other fruit qualities significantly.